1992
DOI: 10.1093/oxfordjournals.aje.a116483
|View full text |Cite
|
Sign up to set email alerts
|

Onset and Disappearance of Gastrointestinal Symptoms and Functional Gastrointestinal Disorders

Abstract: Functional gastrointestinal disorders, including the irritable bowel syndrome, account for up to 40% of referrals to gastroenterologists, but accurate data on the natural history of these disorders in the general population are lacking. Using a reliable and valid questionnaire, the authors estimated the onset and disappearance of symptoms consistent with functional gastrointestinal disorders. An age- and sex-stratified random sample of 1,021 eligible residents of Olmsted County, Minnesota, aged 30-64 years wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
239
0
16

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(284 citation statements)
references
References 0 publications
27
239
0
16
Order By: Relevance
“…13), which calls into question the sensitivity and specificity of the Rome criteria, at least for IBS and functional dyspepsia. This argument is also supported by the observation that patients with functional dyspepsia might eventually present with IBS symptoms at follow-up, whereas others with IBS might switch to functional dyspepsia after 2-10 years 16,17 . Functional dyspepsia overlaps not only with IBS and other functional gastrointestinal disorders but also with some somatic diseases and functional non-intestinal diseases, such as fibromyalgia, overactive bladder and chronic pelvic pain [18][19][20][21] .…”
Section: Epidemiologymentioning
confidence: 80%
“…13), which calls into question the sensitivity and specificity of the Rome criteria, at least for IBS and functional dyspepsia. This argument is also supported by the observation that patients with functional dyspepsia might eventually present with IBS symptoms at follow-up, whereas others with IBS might switch to functional dyspepsia after 2-10 years 16,17 . Functional dyspepsia overlaps not only with IBS and other functional gastrointestinal disorders but also with some somatic diseases and functional non-intestinal diseases, such as fibromyalgia, overactive bladder and chronic pelvic pain [18][19][20][21] .…”
Section: Epidemiologymentioning
confidence: 80%
“…A stable 18.1% prevalence and 9% incidence of IBS at 1 year follow-up was found, suggesting both a significant resolution and emergence of IBS symptoms over time. 59 The difficulty in assessing IBS incidence is illustrated by the following two studies that give a two-fold difference in estimates of incidence, despite using the same diagnosis-linked United Kingdom General Practice Research Database (UKGPRD). Ruigomez and colleagues estimated an IBS incidence of 3 ⁄ 1000 person-years, whereas Jones and colleagues estimated the incidence of IBS to be 1.9 ⁄ 1,000 for men and 5.8 ⁄ 1000 for women.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this trial in the United Kingdom, patients alternate between several days with symptoms and several days without symptoms. The results from the single IBS natural history trial (including those in this systematic review) demonstrated that up to 38% of IBS patients did not meet diagnostic criteria for IBS, and reported prolonged symptom-free periods after 1 yr of follow-up, suggesting that IBS patients may develop a "remission" after a series of symptomatic episodes (19). Longitudinal studies have also been done outside the US, and one study in particular bears reporting (24).…”
Section: Ajg -August 2002mentioning
confidence: 91%
“…Epidemiology of Irritable Bowel Syndrome and abstracts, followed by review of the full manuscripts of potentially relevant articles, identified eight articles that met inclusion criteria (12)(13)(14)(15)(16)(17)(18)(19). Only studies from the United States were found, as there were no published populationbased studies from Mexico or Canada.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation